BRCA1/2 testing: uptake, phenocopies, and strategies to improve detection rates in initially negative families - Fischer, Christine; Sutter, Christian; Voigtländer, Theda (Clinical genetics, 2012)
Fischer C, Engel C, Sutter C, Zachariae S, Schmutzler R, Meindl A, Heidemann S, Grimm T, Goecke TO, Debatin I, Horn D, Wieacker P, Gadzicki D, Becker K, Schäfer D, Stock F, Voigtländer T, on behalf of the German Consortium for Hereditary Breast and Ovarian Cancer. BRCA1/2 testing: uptake, phenocopies, and strategies to improve detection rates in initially negative families. In families with clustering of breast and ovarian cancer, molecular testing of the major susceptibility genes BRCA1/2 helps to identify patients with disease mutations and healthy persons at high risk who can participate in targeted intervention programs. We investigated 5559 families from the German Consortium for Hereditary Breast and Ovarian Cancer included between 1997 and 2008 and treated under clinical routine conditions. In each family an index patient/person had been screened for deleterious mutations in BRCA1/2. Healthy relatives agreed to predictive testing in 888 of 1520 BRCA1/2 mutation-positive families (58%). Of 2646 eligible unaffected first-degree relatives 1143 decided to be tested (43%). In 325 families with BRCA1/2-positive index patients one related BC/OC patient was tested and 39 (12.0%; 95% confidence interval: 8.7-16.0%) discrepant cases found. A second related individual was screened in 163 of 3388 (4.9%) families with BRCA1/2-negative index patient and in eight families a BRCA1/2 mutation was found. In BRCA1/2 mutation-positive families, BC/OC patients lacking the familial mutation have to be expected at a rather high rate. In families with BRCA1/2-negative index patient we recommend a second screening if another patient with a high probability of carrying a BRCA1/2 mutation is available.